A fundamental study of improving thermal interface connection by using silane modified, in-situ formed silver-graphene fillers in epoxy polymers for future semiconductor device packaging. (10th November 2022) - Sun, Zhijian; Wong, Ryan; Liu, Yifan; Yu, Michael; Li, Jiaxiong; Liu, Huilong; An, Dong; Moran, Macleary; Muslu, Ahmet Mete; Wong, Ching-Ping
Abstract: Over the past half-century, the increase of on-chip power and on-chip integration density has created new thermal management challenges for 2.5D/3D semiconductor packaging. High-performance thermal management materials in electronic encapsulation are very important to ensure the performance and reliability of the electronic devices. Graphene-based polymer composites have attracted much attention due to the ultrahigh thermal conductivity and large surface area of graphene. However, graphene nanosheets easily aggregate and lack functional groups on their surfaces, leading to phonon scattering within the interfaces. In this work, silver nanoparticles are in-situ formed on the graphene surface by a facile method, then the graphene-silver nanofillers are modified by (3-Mercaptopropyl)trimethoxysilane (MPTS). MPTS reacts with silver nanoparticles to connect them with epoxy. Also, silver nanoparticles on the surface of graphene can fuse together to form metallurgical joints that connect graphene nanosheets. With the fundamental understanding of sintering mechanisms and reducing two types of thermal interfacial resistances (filler-filler and filler-epoxy interface resistances) simultaneously, the resultant epoxy nanocomposites achieve a high through-plane thermal conductivity of 0.99 W/mK at 8 wt% loading. This corresponds to a 465.7% increase in thermal conductivity as compared to that of neat epoxy. Also, the nanocomposites present a low CTE and high thermal stability. They show strong cooling capability and heat dissipation as thermal interface materials (TIMs) through both experimentation and simulation, providing a promising new insight into thermal management materials to meet the demands of next generation high-power and high-density semiconductor packaging. Graphical abstract: Image 1 Highlights: Thermal interfacial resistance between epoxy and graphene have been demonstrated. Sintering mechanisms of silver-graphene fillers have been investigated. Modified graphene fillers can greatly enhance thermal conductivity of epoxy. Performance of TIMs have been demonstrated by experimentation and simulation.